IMPLEMENTATION OF THE “SI SUPERLARIS” POLICY IN HEIR REGISTRATION SERVICES AT THE GRABAGAN VILLAGE GOVERNMENT, TULANGAN - Yulianto, Jovanca Lintang Arwana; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of digital public service policies through the Si Superlaris application in managing inheritance statements in Grabagan Village, Tulangan District, Sidoarjo Regency. Method: A descriptive qualitative approach was employed, using George C. Edward III’s policy implementation model, which emphasizes communication, resources, implementer disposition, and bureaucratic structure. Data were obtained through interviews, observations, and documentation to ensure validity through triangulation. Results: The findings reveal that the implementation of Si Superlaris aligns with the four dimensions of policy implementation. Communication has been effectively established through socialization and inter-operator communication groups; human resources are considered sufficient; and implementer commitment remains positive. Nonetheless, technical challenges persist, particularly regarding the incompatibility of digital documents with external institutional requirements, limiting full integration. These results underscore the need for cross-sectoral collaboration and continuous system updates to strengthen digital service delivery. Novelty: The originality of this study lies in its examination of the digitization of inheritance administration services at the village level, a relatively unexplored area in public policy research, thereby offering new insights into the role of local governance in advancing digital transformation.